2007
DOI: 10.2214/ajr.07.2711
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Systolic and Diastolic Reconstruction Windows for Coronary CT Angiography Using Dual-Source CT

Abstract: Using dual-source CT, the overall optimal reconstruction window is at 75% of the R-R interval in patients with low or intermediate heart rates. In patients with heart rates of > 80 bpm, systolic reconstructions often yield superior image quality compared with diastolic reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 28 publications
9
62
2
2
Order By: Relevance
“…When we specifically investigated optimal reconstruction intervals for assessment of all coronary artery segments in relation to different HRs, we have come across a similar pattern with prior studies (17), with optimal reconstruction intervals shifting to end-systole with increasing HRs. Relative coronary artery motion during the cardiac phase could be considered the main determinant of coronary segment visibility on CTA.…”
Section: Discussionsupporting
confidence: 60%
“…When we specifically investigated optimal reconstruction intervals for assessment of all coronary artery segments in relation to different HRs, we have come across a similar pattern with prior studies (17), with optimal reconstruction intervals shifting to end-systole with increasing HRs. Relative coronary artery motion during the cardiac phase could be considered the main determinant of coronary segment visibility on CTA.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, a shift of optimal image quality from diastolic to systolic reconstruction intervals in patients with high HRs is reported for 64-detector single-source as well as 64-detector dual-source retrospectively ECG-gated CTCA [12][13][14][15][16][17][18]. Using retrospectively ECG-gated DSCT, Adler et al [17] found the optimal systolic phase of image reconstruction to be between 35% and 50% of the RR interval in patients with HR>65 bpm and Araoz et al [16] reported that optimal image sharpness of the coronary arteries is achieved at 65-70% of the RR interval in patients with HR≤70 bpm and at 35-40% of the RR interval in patients with HR>70 bpm.…”
Section: Discussionmentioning
confidence: 60%
“…The optimal timing of image acquisition to minimise coronary arterial motion artefacts-especially of the mid to distal right coronary artery (RCA)-may shift to systolic intervals in patients with high HRs as diastolic diastasis shortens and eventually disappears with increasing HRs [9,10]. It has been demonstrated with 16-and 64-detector single-source as well as dual-source CT that the best results regarding coronary artery image quality are achieved at middiastolic intervals in patients with low HRs and at systolic intervals in patients with high HRs [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This range of the cardiac cycle was chosen because it has been shown to contain the optimal systolic and diastolic quiescent phases. 3,17 However, since the remainder of the cardiac cycle, i.e., between 80% and 20% is not reconstructed, it is possible that the start of the systolic or end of the diastolic quiescent period may lie outside the 20%-80% reconstructed interval of the cardiac cycle. This is apparent in Fig.…”
Section: A Limitationsmentioning
confidence: 99%